Nationalisation de terres et regime foncier dans le sud-ouest du Nigeria - Francis, P.A. (1986)
Summarises the literature on the alleged defects of traditional systems of land tenure in Nigeria. Reviews the provisions of the land use decree and their implications for rural land tenure.